Penguatan Kesadaran Pendidikan tinggi dalam Keluarga melalui Pendekatan Spiral Sosiospiritualcultural: Studi Pengabdian Masyarakat di Desa Paring Lahung, Kabupaten Barito Utara: Strengthening Awareness of Higher Education in Families through a Socio-Spiritual-Cultural Spiral Approach: A Community Service Study in Paring Lahung Village, North Barito Regency - Widodo, Petrus; Sangalang, Ronald Hadibowo; Alexandro, Rinto; Asi, Natalina; Razzi, Fahrul; Tuah, Tuah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This Community Service activity aims to foster awareness of family education in Paring Lahung Village, Montallat Subdistrict, North Barito Regency, through a socio-spiritual-cultural spiral approach. This approach emphasises the synergy between social, spiritual, and local cultural values in building family self-awareness of the importance of higher education. The activity was conducted in three stages: preparation, implementation, and evaluation, involving 30 participants, comprising students and parents from SMAS PGRI Tumpung Laung. Data was collected through observation, interviews, and pre- and post-test questionnaires. The results showed an increase in students' motivation to pursue higher education (from 32% to 92%), as well as an increase in parental support for their children's education (from 80% to 92%). Participants also demonstrated a new understanding that education is not only an individual achievement but also a form of devotion to God and family. These findings confirm the effectiveness of the Spiral socio-spiritual-cultural approach as a model for family empowerment, grounded in local culture. This programme has the potential to be replicated in other rural areas with similar socio-cultural characteristics.